Distinct nuclear proteins competing for an overlapping sequence of cyclic adenosine monophosphate and negative regulatory elements regulate tissue-specific mouse renin gene expression. - Horiuchi, M (1993)
The mouse renin locus (Ren-1d) exhibits specific patterns of tissue expression. It is expressed in kidney but not submandibular gland (SMG). This locus contains a negative regulatory element (NRE) and a cAMP responsive element (CRE) that share an overlapping sequence. In the kidney, CRE binding proteins (CREB) and NRE binding proteins (NREB) compete for binding to this sequence, with the CREB having a greater affinity. In the SMG, CREB is inactivated by an inhibitory protein, permitting NREB to bind to the sequence, thus inhibiting Ren-1d expression. We hypothesize that the competition between NREB and CREB for this sequence governs tissue-specific expression of mouse renin. We speculate that this may be a general paradigm that determines tissue-specific gene expression.